2020
DOI: 10.31729/jnma.5287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self Induced Abortion by Self-Administration of Abortive Pills among Abortion-related Admissions in a Tertiary Care Centre

Abstract: Introduction: Each year, unsafe medical abortion costs the lives of thousands worldwide. Despite the legalization of abortion in Nepal in 2002, many still seek services from unauthorized sources. This has led to grave consequences including death. Our objective is to find out the prevalence of self-induced abortion by self-administration of abortive pills and related complications. Methods: It is a descriptive cross-sectional study carried out among abortion-related admissions in a tertiary care center f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Thapa et al reported, 37.8% were primigravida and 62.2% were multigravida. 11 This demonstrates that women rely on medical abortion and see it as a better way to space out their pregnancies than taking contraception and preventing undesired pregnancies in the first place. The safe upper gestational age limit for pill intake is seven weeks, according to the MTP Act of India.…”
Section: Discussionmentioning
confidence: 99%
“…Thapa et al reported, 37.8% were primigravida and 62.2% were multigravida. 11 This demonstrates that women rely on medical abortion and see it as a better way to space out their pregnancies than taking contraception and preventing undesired pregnancies in the first place. The safe upper gestational age limit for pill intake is seven weeks, according to the MTP Act of India.…”
Section: Discussionmentioning
confidence: 99%
“…Among women who had a self-induced abortion by self-medication, 13.5% had an ectopic pregnancy and among them, one was the case of ovarian molar pregnancy. 10 Standard treatment options for GTD differ depending on the implantation location and stage of the disease. Treatment includes chemotherapy, suction evacuation, hysterectomy, or a combination of all.…”
Section: Discussionmentioning
confidence: 99%
“…Also, about 23.5% of women with ectopic pregnancy had a history of consuming MA pills 9 but self‐medication with abortive medications complicating ovarian molar pregnancy is rare. Among women who had a self‐induced abortion by self‐medication, 13.5% had an ectopic pregnancy and among them, one was the case of ovarian molar pregnancy 10 …”
Section: Discussionmentioning
confidence: 99%
“…Examen de orina para cuantificar la diuresis y presencia de alguna infección asociada o descartar enfermedad renal. Pruebas de VDRL para descartar sífilis, Elisa para VIH y prueba para confirmar efectivamente un embarazo (cuantificación de la hormona coriónica humana subunidad beta) (31).…”
Section: Base Teóricaunclassified